2018
DOI: 10.1002/met.1749
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of global warming on precipitation patterns in India

Abstract: The past few decades have witnessed a change in precipitation patterns around the world. This change includes an increase in heavy precipitation and a decrease in light and moderate precipitation. Global/regional warming has been attributed as one of the major factors causing the observed change in precipitation patterns. Past studies over the Indian region have not focused much on quantification of the impact of warming on changes in precipitation patterns. The present research quantifies the impact of warmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…These results were in agreement with the previous finding about an decrease in annual precipitation over China [31]. In other regions of the world, similar results were also found in the Mediterranean, India, Turkey, and East Africa [54][55][56][57]. However, Song, Achberger and Linderholm [41] found that the total amount of rain-season precipitation showed an increasing trend in China from 1961 to 2008.…”
Section: Discussionsupporting
confidence: 92%
“…These results were in agreement with the previous finding about an decrease in annual precipitation over China [31]. In other regions of the world, similar results were also found in the Mediterranean, India, Turkey, and East Africa [54][55][56][57]. However, Song, Achberger and Linderholm [41] found that the total amount of rain-season precipitation showed an increasing trend in China from 1961 to 2008.…”
Section: Discussionsupporting
confidence: 92%
“…Atmospheric water vapour plays a critical role in governing precipitation patterns (Trenberth et al, 2003;Mishra and Liu, 2014;Mishra, 2019). Mishra and Liu (2014) reported an increase in heavy precipitation and a reduction in light and moderate precipitation as a result of increased atmospheric water in a warming environment.…”
Section: Introductionmentioning
confidence: 99%
“…A rise of 1.5°C in global mean temperature from the preindustrial era can increase the three hourly precipitation maxima by 20% (Ali and Mishra 2018). Mishra (2019) also attributes the heavy precipitation events to global warming, speci cally to increased extreme precipitation and a decrease in moderate and light precipitation. This study shows that for a 1.0°C increase in regional warming, about 4.98% ± 1.26% increase can occur in the precipitable water vapour content.…”
Section: Introductionmentioning
confidence: 99%